2020
DOI: 10.15701/kcgs.2020.26.3.79
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Design and Effect of Feedback for Virtual Reality Exercise Posture Training

Abstract: It is important to exercise in the correct posture in order to increase the exercise effect of the core exercise. This paper introduces a system that can train an exercise posture by providing feedback so that a user who performs core exercise in a virtual reality environment can take an accurate posture. It targeted three core movement postures, such as squat, lunge, and bridge, and provides visual feedback and haptic feedback to the user to take an accurate posture. The reference posture is generated by adju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…In the previous studies, exercise with feedbacks showed better results than none feedback exercise groups [15,16]. Also, self-training can occur overuse injuries [9]. Therefore, this type of device can be beneficial to special occupations, such as FFs who has irregular schedule due to emergencies.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…In the previous studies, exercise with feedbacks showed better results than none feedback exercise groups [15,16]. Also, self-training can occur overuse injuries [9]. Therefore, this type of device can be beneficial to special occupations, such as FFs who has irregular schedule due to emergencies.…”
Section: Introductionmentioning
confidence: 88%
“…By Kinect, KMR can convert a user's exercise performance into data in a non-face-to-face manner. It is commonly applied with a software and were used as a game, exercise, or assessment [8][9][10][11][12]. Another major component of this device is its mixed reality (MR) environment.…”
Section: Introductionmentioning
confidence: 99%